Implementasi Nilai-Nilai Pancasila Melalui Aksi Penanaman 10.000 Pohon untuk Pelestarian Hutan - Jihan Salma Valencia; Nur Agfanda Inmala; Laura Enjelia Fernandes; Bunga Salsya Mulya; Dina Rosyidah (Jurnal Pendidikan dan Kewarganegara Indonesia, 2026)
Indonesia's tropical forests face increasing degradation from land conversion, illegal logging, and seasonal fires. This study examines how Pancasila values can serve as an ethical framework for tree planting actions aimed at forest conservation, specifically focusing on a 10,000-tree planting initiative. Using a literature review method, this study analyzes community service reports and academic articles on reforestation and Pancasila-based environmental management. The findings show that all five principles of Pancasila are interconnected and form a unified ecological ethic. The first principle provides a spiritual foundation for gratitude and responsibility toward nature; the second promotes fairness in sharing environmental burdens and benefits; the third enables cross-regional cooperation; the fourth places deliberation at the center of conflict resolution between conservation and land use interests; and the fifth ensures that conservation outcomes are distributed equitably across communities and generations. This study recommends that large-scale planting programs be evaluated not only by number of trees planted, but by the extent to which the process reflects the values of mutual cooperation, justice, and deliberation central to Pancasila.